Expression of Heat Shock Protein 105 in Cutaneous Squamous Cell Carcinoma: Correlation with Clinicopathological Characteristics - Jia M; Li FZ; Ye Q; Chen KJ; Fang S (Dove Medical Press, 2021)
Meng Jia, Feng-Zeng Li, Qian Ye, Ke-Jun Chen, Sheng Fang Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Sheng FangDepartment of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of ChinaEmail fangshengderm@163.comBackground: Heat shock proteins (HSPs), a group of heat stress proteins, are characterized by highly conserved properties. Malignant transformation is a cellular stress, and the expression of HSPs may be affected during this process. Heat shock protein 105 (HSP105) is a protective protein that has long been observed in many cancer types, but little attention has been given to cutaneous squamous cell carcinoma (CSCC). As such, the objectives of this study were to observe the expression of HSP105 on CSCC and evaluate its correlation with clinicopathological characteristics.Methods: This retrospective study enrolled 60 patients with CSCC. The patients’ clinical data, including sex, age, tumor location, tumor type, and degree of pathological differentiation, were collected. The expression of HSP105 was measured by Western blot and immunohistochemical staining.Results: HSP105 expression was decreased in CSCC (HSCORE=0.65 (0.30, 1.98)) compared with normal skin (HSCORE=2.20 (1.50, 2.80)) (P< 0.001). These results were consistent with the Western blot analysis. HSP105 immunostaining of Bowen disease (HSCORE=1.28 (1.08, 2.40)) revealed higher expression than in verrucous carcinoma (HSCORE=0.30 (0.23, 0.85)), keratoacanthoma (HSCORE=0.53 (0.29, 0.93)) and acantholytic squamous cell carcinoma (HSCORE=0.53 (0.41, 0.68) (P< 0.01)). Poorly differentiated CSCC showed significantly higher expression of HSP105.Conclusion: Our study reveals for the first time that the expression of HSP105 is decreased in CSCC. We suggest that the molecular mechanisms underlying the differential expression of HSP deserve a more rigorous future study, the results of which might explain its role in carcinogenesis and its potential as a target for selective tumor therapy.Keywords: heat shock protein 105, cutaneous, squamous cell carcinoma, expression